Intracellular delivery of doxorubicin encapsulated in novel pH-responsive chitosan/heparin nanocapsules - Thomas MB (Dove Medical Press, 2013)
Midhun B Thomas,1,* Krishna Radhakrishnan,1,* Divya P Gnanadhas,2,* Dipshikha Chakravortty,2 Ashok M Raichur1,31Department of Materials Engineering, 2Department of Microbiology and Cell Biology, Indian Institute of Science, Bangalore, India; 3Department of Applied Chemistry, University of Johannesburg, Doornfontein, South Africa*These authors contributed equally to this workAbstract: A novel polyelectrolyte nanocapsule system composed of biopolymers, chitosan and heparin has been fabricated by the layer-by-layer technique on silica nanoparticles followed by dissolution of the silica core. The nanocapsules were of the size range 200 ± 20 nm and loaded with the positively charged anticancer drug doxorubicin with an efficiency of 89%. The loading of the drug into the capsule happens by virtue of the pH-responsive property of the capsule wall, which is determined by the pKa of the polyelectrolytes. As the pH is varied, about 64% of the drug is released in acidic pH while 77% is released in neutral pH. The biocompatibility, efficiency of drug loading, and enhanced bioavailability of the capsule system was confirmed by MTT assay and in vivo biodistribution studies.Keywords: drug delivery, layer-by-layer, electrostatic interaction, biocompatible